The potential for Scottish cultivated topsoils to lose or gain soil organic carbon. (22nd November 2012) - Lilly, A.; Baggaley, N. J.
Abstract Scotland's cultivated topsoils are rich in carbon with a median soil organic carbon (SOC) content of ca. 3.65%. The storage of carbon in soil is a means to offset GHG emissions, but equally carbon losses from soils can add to these emissions. We estimate the amount of carbon stored in Scottish cultivated mineral topsoils (246 ± 9 Mt), the potential carbon loss (112 ± 12 Mt) and the carbon storage potential of between 150 and 215 Mt based on national‐scale legacy data with uncertainty around the estimate due to error terms in predicting bulk densities for stock calculations. We calculate that Scotland's mineral cultivated topsoils hold the carbon equivalent of around 18 years of GHG emissions (based on 2009 emissions from all sources). We also derive a theoretical carbon saturation potential using a published, linear relationship with the <20‐μm mineral fraction (116 ± 14 Mt). Although the calculated uncertainties are quite small, care needs to be taken when using the results of such analyses as a policy instrument, and while the potential storage capacity seems large, it is unlikely to be achieved while still maintaining current land use patterns in Scotland. The methodology relies on legacy data (which may not reflect the current status of Scottish cultivated topsoils) and on summary statistics calculated from national‐scale data; however, those land management strategies that may mitigate GHG emissions are likely to be implemented at the field scale.